A new porous Co(ii)-metal–organic framework for high sorption selectivity and affinity to CO2 and efficient catalytic oxidation of benzyl alcohols to benzaldehydes. Issue 20 (5th May 2021) - Wu, Yun-Long; Yang, Rong-Rong; Yang, Guo-Ping; Yan, Yang-Tian; Su, Xiao-Lei; He, Xin-Hai; Song, Yan-Yan; Ma, Zheng-Sheng; Wang, Yao-Yu
Abstract : A new porous Co(ii )-MOF I has been prepared. Gas sorption and catalytic experiments show that the guest-free sample I′ shows the high capacity and selectivity to CO2 over CH4 and catalytically oxidize benzyl alcohols efficiently into benzaldehydes. Abstract : Herein, we report a new 3D porous Co(ii )-based metal–organic framework catalyst (Me2 NH2 )2 [Co3 (L)2 (H2 O)2 ]·2DMF (MOF I ), which has been successfully prepared by using Co(ii ) ions and rigid V-shaped 3, 5-di(2, 4-dicarboxylphenyl)pyridine (H4 L) via the solvothermal reaction. Structural analysis reveals that I displays a porous structure with the pore size of 16.2 × 7.2 Å 2 based on the trinuclear [Co3 (COO)4 (H2 O)2 N2 ] secondary building units (SBUs). Gas sorption experiments on the guest free sample I′ reveals a high capacity and selectivity to CO2 over CH4 . And further, the catalytic explorations of the I′ -catalyzed system (I′ : 3 mol%; proline: 40 mol%; CH3 CN: 2 mL) reveal that benzyl alcohols with different structures can be efficiently transformed into benzyl alcohols without by-products under mild conditions.